2017
DOI: 10.1002/pbc.26887
|View full text |Cite
|
Sign up to set email alerts
|

An initial health economic evaluation of pharmacogenomic testing in patients treated for childhood cancer with anthracyclines

Abstract: The newly identified genetic variants associated with the risk of ACT provide information that allows a more reliable prediction of the risk of ACT for a given patient and can be obtained at a very moderate cost, which is expected to lead to meaningful progress in reducing harm and costs associated with ACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Using actual data from the Prospective Comparison of Angiotensin Receptor-Neprilysin Inhibitor with Angiotensin-Converting-Enzyme Inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial (PARADIGM-HF), Packer coauthored a letter with Claggett et al 2 that derived actuarial estimates of age-specific expected survival times and found that PARADIGM-HF-eligible patients aged 55 years have a projected life expectancy of 11.6 years while receiving enalapril and 12.9 years with sacubitril/valsartan, a difference of 1.3 years. 2 Similar survival estimates were reported for PARADIGM-HF-eligible patients aged 65 years (10 years for enalapril vs 11.4 years for sacubitril/valsartan). 2 These survivals are clearly at or over the 10-year duration that Packer states is "irrelevant" for patients after heart failure.…”
Section: Conflict Of Interestsupporting
confidence: 70%
See 1 more Smart Citation
“…Using actual data from the Prospective Comparison of Angiotensin Receptor-Neprilysin Inhibitor with Angiotensin-Converting-Enzyme Inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial (PARADIGM-HF), Packer coauthored a letter with Claggett et al 2 that derived actuarial estimates of age-specific expected survival times and found that PARADIGM-HF-eligible patients aged 55 years have a projected life expectancy of 11.6 years while receiving enalapril and 12.9 years with sacubitril/valsartan, a difference of 1.3 years. 2 Similar survival estimates were reported for PARADIGM-HF-eligible patients aged 65 years (10 years for enalapril vs 11.4 years for sacubitril/valsartan). 2 These survivals are clearly at or over the 10-year duration that Packer states is "irrelevant" for patients after heart failure.…”
Section: Conflict Of Interestsupporting
confidence: 70%
“…Interestingly, RARG (rs2229774) was shown to increase the transcription of topoisomerase IIβ. 2 Thus, patients who developed anthracycline-induced cardiotoxicity are predicted to have higher topoisomerase IIβ expression. This is consistent with the new paradigm described in our review.…”
Section: Jennifer Cautela MD Nathalie Lalevee Phd Franck Thuny Md Phdmentioning
confidence: 99%
“…All other patients should be considered at moderate genetic risk. An initial health economic evaluation of pharmacogenomic testing in patients treated for childhood cancer with anthracyclines suggests that information gained from the pharmacogenomic test could reduce mortality by approximately 17% and reduce costs by about 6% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was comparable to PPV of 34.4% and NPV 90.9% obtained in other studies 9,19,41 . With current care, the estimated average lifetime cost of DIC is $8,667 per treated patient 42 . Our test will reduce DIC related life cost and deaths in 33% of patients who carry the risk variants.…”
Section: Discussionmentioning
confidence: 99%